Investigating counselors' lived experiences of ethical perception and its challenges in the counseling profession - Nafiseh HosseiniBiouky; Kiiumars Farahbakhsh; Hossein Salimi Bejstani; Massoumeh esmaeily (اخلاق وحیانی)
In the counseling process, counselors are forced to understand ethically on various issues, and there are many challenges in this path, and some of them are influential. For this reason, this research examines the experiences of counselors on ethical perception and its challenges. The methodology of this research was qualitative and with a phenomenological approach. The studied community was formed by consultants who had at least 5 years of experience. Among them, a sample of 20 people was selected by purposeful sampling, the sampling process took until saturation was reached. The data collection method was a semi-structured interview. The analysis of the collected data was carried out using the Collaizi method. After analyzing the data, 36 sub-themes and 5 main themes were obtained (characteristics, moral-professional development, value and belief system, sensitivity to cultural issues, awareness of system shortcomings). The results of the research findings, in addition to creating insight and awareness about the challenges of counselors in moral perception, can be used for planning to solve the problems and issues of this group, clients and beneficiary organizations.